Can the market affect non-government banking returns during COVID-19 pandemic? - Citra Salniati Mallisa; Febriani Timbang; Marni Palullungan; Olfin M. Appulembang (Yayasan Widyantara Nawasena Raharja, 2022)
At the beginning of the era of the Covid-19 pandemic, returns on the capital market became increasingly uncertain, especially for non-government-owned banks in Indonesia. The purpose of this study is to determine the relationship between market movements and returns from non-government banks in Indonesia. The results of the analysis on MEGA and BNGA in the range 5 June 2020 to 30 December 2021 show that the two banks have the same stock return. Empirically, this study finds that stock returns and market returns have unidirectional relationship even though the two banks have different risks.